Pengaruh Persepsi Kualitas Pelayanan dan Persepsi Nilai Terhadap Kepuasan Serta Dampaknya Pada Loyalitas Pelanggan Maskapai Penerbangan - Annisa Budiansari; Sujana Sujana (Jurnal Ilmiah Pariwisata Kesatuan, 2021)
This study aims to determine : The effect of perception of service quality on customer satisfaction, The effect of customer value perception on customer satisfaction, and And the impact of customer satisfaction on customer loyalty. This study uses the independent variable (service quality perception, customer value perception), and the dependent variable (customer satisfaction and customer loyalty). The sample method used in this study is the roscoe method and the Analysis Tool used in this study is AMOS version 23. With the number of 200 respondents selected are people who have used Batik Air Indonesia's flight services in the city of Bogor. Based on the research, it can be concluded that there are three hypotheses that have positive and significant influence, namely: The first hypothesis is the perception of service quality and customer satisfaction has an influence and significant with the results of the t-test of 4.039 greater than t-table. The second hypothesis is the perception of customer value on customer satisfaction has an influence with a negative t-test that is equal to -1.529 smaller than t-table. The third hypothesis is customer satisfaction Customer loyalty has a positive and significant impact with the t-test result of 4.039 greater than t-table. Keywords: Perception, influence, impact, Service Quality, Customer Value, Customer Satisfaction, Customer Loyalty, Batik Air Indonesia.